Lithopedion in a Geriatric Patient - Ricaurte Sossa, Andrés; Bolaños, Henry; Ricaurte Fajardo, Andrés; Burgos, Ángela Camila; Garcia, Valentina; Muñoz, Paola; Rosselli, Diego (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2019)
Lithopedion (lithos = rock and paidion = child) is a rare condition that only occurs in 1.5 to 1.8% of extrauterine pregnancies and in 0.00045% of all pregnancies. It consists of an ectopic pregnancy in which the fetus dies but cannot be reabsorbed by the mother's body, which then coats it in a calcium-rich substance. We present the case of a 77-year-old woman with an incidental diagnosis of a lithopedion, which had been retained in her left pelvis for presumably 40 years.
Keywords: lithopedion; ectopic pregnancy; geriatric